Lithospheric detachment of India and Tibet inferred from thickening of the mantle transition zone. (July 2016) - Duan, Yaohui; Tian, Xiaobo; Liu, Zhen; Zhu, Gaohua; Nie, Shitan
Graphical abstract: Highlights: We used a modified receiver function stacking technique. The mantle transition zone (MTZ) is thickened beneath southern Tibet and Himalaya. Thickening below southern Tibet may be the result of a detached thickened Tibet mantle lithosphere. Thickening below the Himalaya is most likely caused by a lithospheric slab detached from the Indian plate. Abstract: To spatially and temporally interpret eruptive volcanic activity and plateau uplift, the dynamic model of the Himalayan–Tibetan orogen requires several scenarios in which the deep part of the lithosphere is removed. The removed cold, dense material sank deeply and may rest in the mantle transition zone, which is considered as the graveyard for descending mantle lithosphere. Beneath the Himalayas and southern Tibet, stacking teleseismic P-wave receiver functions reveal thickening of the mantle transition zone (MTZ), which is caused by decreasing temperatures. We interpret the MTZ thickening beneath southern Tibet as being a result of a remnant of detached thickened Tibet mantle lithosphere, whereas the other thickening is most likely caused by a lithospheric slab that detached from the Indian plate and is sinking into the MTZ beneath the Himalayas.